The therapeutic effects of glucagon-like peptide-1 receptor agonists and metformin on polycystic ovary syndrome: A protocol for systematic review and meta-analysis. Issue 23 (11th June 2021) - Ma, Ruilin; Ding, Xuesong; Wang, Yanfang; Deng, Yan; Sun, Aijun
Abstract: Background: Obesity and insulin resistance (IR) are common in polycystic ovary syndrome (PCOS), which contribute to reproductive and metabolic abnormalities. Metformin increases insulin sensitivity, but it is associated with unsatisfied benefits of weight loss. Recent studies have reported that glucagon-like peptide 1 (GLP-1) receptor agonists improve IR and reduce weight in women with PCOS. We conducted a systematic review and meta-analysis to compare the effects between GLP-1 receptor agonists and metformin, and between GLP-1 receptor agonist-metformin combination and GLP-1 receptor agonists in overweight/obese women with PCOS on anthropometric, metabolic, reproductive outcomes. Methods: Databases including PubMed, EMBASE, Web of Science, and Cochrane Library were selected to search for randomized controlled trials (RCTs) published in English up to March 2020. Eligible studies were identified according to the inclusion criteria. The primary outcomes included menstrual frequency, body mass index (BMI), total testosterone, and the homeostatic model assessment of insulin resistance. GRADE criteria were implemented to assess the quality of evidence for primary outcomes. Results: Seven RCTs were selected for analysis, comprising 464 overweight/obese women with PCOS. In the low-quality evidence, a meta-analysis demonstrated that GLP-1 receptor agonists showed better effects relative to metformin on the reduction of body mass index (mean difference − 1.72; 95% confidence interval −2.46 to −0.99, P  < .001) and homeostatic model assessment of insulin resistance (standard mean difference −0.37; 95% confidence interval − 0.60, − 0.15, P  = .001). Moreover, the combination therapy exhibited similar effects on primary outcomes relative to GLP-1 receptor agonist alone. GLP-1 receptor agonists were also found to be associated with lower abdominal girth compared to metformin. A meta-analysis of gastrointestinal discomfort showed no significant difference between GLP-1 receptor agonist and metformin therapies, and between the combination therapy and GLP-1 receptor agonist alone. Conclusions: GLP-1 receptor agonists appear to be more beneficial for weight loss and IR improvement compared to metformin for overweight/obese women with PCOS. However, the combination treatment displays comparable effects with GLP-1 receptor agonist alone. The incidence of gastrointestinal discomforts was similar in different groups. However, the quality of the body of evidence is "low." Further prospective RCTs and cost-effectiveness analyses are also warranted to guide GLP-1 receptor agonists to treat women with PCOS. Abstract : Supplemental Digital Content is available in the text